Covalent triazine framework-decorated phenyl-functionalised SBA-15: its synthesis and application as a novel nanoporous adsorbent. (2nd August 2019) - Soltani, Roozbeh; Shahvar, Ali; Gordan, Hasti; Dinari, Mohammad; Saraji, Mohammad
Abstract : Novel covalent triazine framework-decorated phenyl-functionalised SBA-15 was synthesised via a facile AlCl3 -catalysed Friedel–Crafts strategy and applied as an adsorbent for dye removal. Abstract : This study elucidates, for the first time, a new and facile synthesis approach applying an AlCl3 -catalysed Friedel–Crafts strategy to synthesise a porous organic–inorganic hybrid material consisting of a covalent triazine-based framework (CTF) and phenyl-functionalised SBA-15 for the adsorption of methylene blue from aqueous media. The CTF units were successfully grafted inside the hexagonal channels of mesoporous silica through an in situ formation method. The as-prepared CTF-decorated phenyl-functionalised SBA-15 (CTF-Ph-SBA-15) was characterised using different techniques, including FT-IR, FE-SEM, EDX, XRD, and N2 adsorption–desorption analysis. The effects of sample pH, initial methylene blue concentration, contact time, adsorbent dosage, and temperature were systematically investigated. Both linear and non-linear forms of various kinetic and equilibrium isotherm models were applied. The kinetic and isotherm regression results showed that the adsorption of methylene blue onto the adsorbent more accurately followed pseudo-second-order kinetic and Langmuir isotherm models. Owing to the abundance of chemically active aromatic groups on the surface of the adsorbent, a high removal efficiency (adsorption capacity of 569 mg g −1 ) was observed under the optimum conditions.